The Unique Qualities of Junior Cycle Visual Art Education in Ireland. - Buttle, Avril; Mullaney, Isobelle (International Journal of Art & Design Education, 2023)
The aim of this paper is to ascertain the main subject qualities in Junior Cycle (JC) Visual Art (VA) in The Republic of Ireland, and whether these qualities are unique to the subject. The context of JC VA education is outlined through the exploration of its values, aims and objectives as well as investigating the subject's unique qualities. A mixed methods research approach was used to analyse three years of Department of Education Subject Inspection Reports for VA to explore the qualities of VA education. Seven published JC Subject specifications, including the VA specification were analysed using word frequency measurements with the aim of exploring the qualities of JC VA and whether these qualities are unique to the subject. Semi‐structured interviews were also held to explore the issues arising and aim to capture some of the thoughts of VA curriculum experts, school leaders and VA teachers. Through the analysis of word frequencies, it can be concluded that the VA specification highlights creativity, problem‐solving, collaboration and reflecting as dominant qualities in VA education and similarly, the Inspection Reports present the same findings. However, it is important to note that these qualities are also found in other subject areas though not as strongly or frequently. The interview process highlighted similar findings concluding that VA education "lends itself" to the above qualities however the subject cannot claim them as solely unique to the VA classroom.